The Harmonization of Pancasila Values and the 1945 Constitution in Resolving Modern Electoral Disputes Based on the Principle of Rule of Law - Callista Yo, Beatrice; Wartoyo, Franciscus; Cheryl, Livia; Maurent, Vanessa (Journal of Law, Politic and Humanities, 2025)
This research aims to analyze the correlation of modern election dispute resolution in a constitutional state in the context of the basic constitution, namely the 1945 Constitution and Pancasila. Using normative qualitative research methods, this research focuses on studying the application of basic state principles in resolving election disputes in Indonesia. The elections held were based on the principles of democracy and popular sovereignty in Article 1 paragraph 3 of the 1945 Constitution which often gave rise to disputes, which ultimately threatened political and legal stability. Therefore, it is important to ensure dispute resolution is in accordance with the values contained in the 1945 Constitution and Pancasila, especially the fourth principle which emphasizes deliberation in representative deliberations. The research results show that harmonization between the values of Pancasila and the principles contained in the 1945 Constitution will result in a crucial role in ensuring fair, transparent and legally valid dispute resolution. Application of principles rule of law in this process can strengthen the legitimacy of election results and increase public trust in the democratic process. With this, the application of these two foundations can maintain political and legal stability in Indonesia, as well as create an electoral system of higher quality and integrity (Constitutional Court, 2023). It is hoped that this research can contribute to strengthening the legal and democratic system in Indonesia.